2021
DOI: 10.1080/23311908.2021.1880258
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of a Multiple Intelligences Teaching Approach: Classroom engagement and physically disabled learners

Abstract: The present mixed-methods classroom-based study investigated whether the provision of multiple intelligences teaching approach to physically disabled learners could contribute to activating multiple intelligences and have a positive impact on their classroom engagement. To address this issue, three intact classes of 10 Iranian physically disabled learners participated in this study. In so doing, the study utilized an experimental design with 10 participants in the control group and 20 participants in two exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Thus, it will affect indirectly when enjoying the beauty of nature. Subjects with an auditory learning style are quite weak in this intelligence because they will tend to use their sense of hearing rather than their sight, while to enjoy nature, the sense of sight is more dominant (Ghaznavi et al, 2021). Subjects with kinesthetic learning styles have high naturalist intelligence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it will affect indirectly when enjoying the beauty of nature. Subjects with an auditory learning style are quite weak in this intelligence because they will tend to use their sense of hearing rather than their sight, while to enjoy nature, the sense of sight is more dominant (Ghaznavi et al, 2021). Subjects with kinesthetic learning styles have high naturalist intelligence.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the intelligence possessed by individuals is influential in solving the problems faced (Rahbarnia et al, 2014). The intelligence in question is Gardner Intelligence which is assisted by teachers, students and parents to understand various ways of learning and developing various kinds of intellectual strengths and life skills of students (Ghaznavi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have provided evidence of MI theory’s semantic effectiveness in inspiring differentiated teaching and learning in the classroom (e.g., Modirkhamene and Azhiri, 2012 ; Milić and Simeunović, 2017 ; Koçak Altundağ, 2018 ; Ghaznavi et al, 2021 ; Shahzada et al, 2021 ). Semantic effectiveness here means that MI theory’s use of the word intelligences seemed to be interpreted as nearly synonymous or at least overlapping with preferences; therefore, its conceptual framing interfaced readily with learning styles theory.…”
Section: Discussion Of Teaching Implicationsmentioning
confidence: 99%
“…The issue, again, seems to be predicated on the semantics of MI theory in its use of the word intelligences. Other studies have emphasized contextual interpretation with statistical data analysis involving in-service teachers or preservice teachers to provide evidence of MI theory’s qualitative effectiveness in the multiple-subject curriculum of elementary school to secondary school science and mathematics (e.g., Baş and Beyhan, 2010 ; Modirkhamene and Azhiri, 2012 ; Milić and Simeunović, 2017 ; Koçak Altundağ, 2018 ; Ghaznavi et al, 2021 ; Shahzada et al, 2021 ). These case studies further support the efficacy of MI theory in classroom practice.…”
Section: Comparative Literature Reviewmentioning
confidence: 99%
“…Using the teaching style of Grasha (1996) and Shaaria et al (2014) found a positive correlation between teaching styles and learners’ academic engagement. In another study, Ghaznavi et al (2021) inspected the role of teaching multiple intelligences in learner engagement, and they found out that this type of teaching approach can enhance learner multiple intelligence, which in turn, develops learner academic engagement.…”
Section: Literature Reviewmentioning
confidence: 99%